Where do you stand? eight moral issues confronting today's Christians - Higgins, Gregory C., 1960- (New York : Paulist Press, 1995)
"This book offers a way of reflecting on eight "life" issues, ranging from sex to capital punishment. It doesn't give answers. It does ask questions. Each issue is explored by a process that offers mature arguments from proponents of different views, yet that leads the reader to make a personal commitment to one course or another. The process consists of concrete situations that put the moral issue in the real-life perspective; a detailed examination of the underlying questions, with arguments supporting each side; discussion questions for group interaction or personal reflection; and suggested readings, resources for those who wish to pursue the questions in more depth."--BOOK JACKET.
Where do you stand on moral reasoning? -- Where do you stand on reproductive technology? -- Where do you stand on abortion? -- Where do you stand on sexual ethics? -- Where do you stand on social justice? -- Where do you stand on euthanasia? -- Where do you stand on war? -- Where do you stand on capital punishment?
Includes bibliographical references (p. 113-119).
Description based on print version record.
Keywords: Christian ethics -- Catholic authors; Christelijke ethiek; RELIGION / Christian Theology / Ethics; Electronic books